A geografia militar no planejamento e na execução das operações militares na Região Sul do Brasil - Vargas, José Nilton Silva (2017)
The themes Defense, although uncommon in the Brazilian geographic research, are increasingly common in other areas of knowledge, particularly among anthropologists, historians, graduates of international relations, administrators and political scientists. It can therefore be a little expression of this research theme in the contemporary geography. In this sense, the present study aims to: identify and assess the extent to which military professionals, 3rd Military structure Organizations Division of the Army, in charge of the field study; and the planning and execution of military operations, know and apply the concepts of Military Geography in its operational activities. The methodological support for the organization of the dissertation will be based on the methods Observational and Monographic procedures. This study is structured as a qualitative research approach with exploratory and descriptive goals, using the Field Research and Case Study. It is hoped that the research answer the question: What is the level of knowledge and the use of military geography, professionals involved in planning and conducting military operations, as part of the Southern Military Command, responsible for a geographical area represented by the Region southern Brazil, leaning over a border region with Argentina, Paraguay and Uruguay?